Hole in the Wall: Informed Short Selling ahead of Private Placements - Henk Berkman; Michael McKenzie; Patrick Verwijmeren (Tinbergen Institute, 2013)
Companies planning a private placement typically gauge the interest of potential buyers before the offering is publicly announced. Regulators are concerned with this practice, called wall-crossing, as it might invite insider trading, especially when the potential investors are hedge funds. We examine privately placed common stock and convertible offerings and find widespread evidence of pre-announcement short selling. We show that pre-announcement short sellers are able to predict announcement day returns. The effects are especially strong when hedge funds are involved and when the number of buyers is high.
Keywords: G32; 330; Insider trading; Hedge funds; Private placements; Wall-crossing; Short-selling